Patient choice improves self-efficacy and intention to complete tuberculosis preventive therapy in a routine HIV program setting in Uganda - Lim, Rachel K.; Semitala, Fred C.; Atuhumuza, Elly; Sabiti, Laban; Namakula-Katende, Jane; Muyindike, Winnie R.; Kamya, Moses R.; Dowdy, David; Cattamanchi, Adithya (PLoS One, 2021)
A 12-dose weekly regimen of rifapentine plus isoniazid (3HP) is recommended for the prevention of active tuberculosis (TB); however, it is unclear whether 3HP should be provided by directly observed therapy (DOT) or self-administered therapy (SAT). In addition, the introduction of patient informed choice between delivery modalities may have a positive impact on factors leading to treatment completion. The authors randomized 252 participants with HIV to a hypothetical scenario of providing preventive therapy by either DOT or an informed choice between DOT and SAT. Out of 104 participants who were randomized to a choice between DOT and SAT, 103 chose therapy by SAT. Participants rated their level of confidence and intention to complete therapy. Compared to those assigned to the DOT scenario, patients assigned to the choice scenario expressed greater confidence and intention to complete preventive therapy. Convenience and travel required to complete 3HP therapy were important factors in deciding between delivery modalities. Those assigned to DOT identified more barriers to completing therapy than those given a choice. Empowering patients to make informed decisions about how they receive TB preventive therapy may improve completion rates.
Keywords: Patients; Therapy; Tuberculosis; HIV; Uganda; Self-efficacy